2002
DOI: 10.1038/sj.bjc.6600044
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and cisplatin in a multimodality treatment for locally advanced non-small cell lung cancer

Abstract: The role of new cytotoxic agents like gemcitabine has not yet been proven in the neoadjuvant settings. We designed a phase II study to test the feasibility of using gemcitabine and cisplatin before local treatment for stage III non-small cell lung cancer patients. Patients received three cycles of induction chemotherapy of gemcitabine (1000 mg m 72 , days 1, 8, 15) and cisplatin (90 mg m 72 , day 15) every 4 weeks before evaluation for operability. Operable patients underwent radical resection. Inoperable pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
8
1
1
Order By: Relevance
“…When evaluating our results in review of the literature, a few differences are noteworthy. Firstly, although comparable to response rates in advanced NSCLC [14][15][16], our response rate of 34% was relatively low compared with previous studies using gemcitabine/cisplatin in the neoadjuvant setting [11,13]. We cannot explain this difference, other than that the actual response might have been underestimated on radiological imaging.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…When evaluating our results in review of the literature, a few differences are noteworthy. Firstly, although comparable to response rates in advanced NSCLC [14][15][16], our response rate of 34% was relatively low compared with previous studies using gemcitabine/cisplatin in the neoadjuvant setting [11,13]. We cannot explain this difference, other than that the actual response might have been underestimated on radiological imaging.…”
Section: Discussioncontrasting
confidence: 72%
“…Thereafter, treatment preferably consisted of 2-4 cycles of gemcitabine (1250 mg/m 2 ) and cisplatin (75 mg/m 2 ), a regimen that has been studied by van Zandwijk et al [11]. In several phase II and III studies, this doublet produced response rates up to 70% [13], and was reported to be more effective than combinations of cisplatin-etoposide or mitomycin-ifosfamide-cisplatin [14][15][16].…”
Section: Induction Therapy and Restagingmentioning
confidence: 97%
“…Before the FDA's approval of epidermal growth factor receptor (EGFR) inhibitors to treat non–small cell lung cancer (NSCLC) in 2003, the overall survival for advanced lung cancer patients treated with chemotherapy was similar for Asian and Western countries. 5 8 However, the prognosis of lung cancer became different after the introduction of EGFR inhibitors. Lung cancers with EGFR mutations are more likely to be adenocarcinoma and occur more often in women, East Asians, and nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…However, cancer chemotherapy has progressed since its introduction into clinical practice and represents the most promising treatment modality. Various chemotherapy drugs, including doxorubicin, 5‐fluorouracil, cisplatin, etoposide and gemcitabine, have been used to treat lung cancer (Scarpati et al ., 2001; Worden & Kalemkerian, 2000; Yang et al ., 2002). But all of these anticancer drugs affect not only pathological tumour cells, but also normal cells, especially bone marrow cells or intestinal epithelia with high turnover rate, causing serious complications and toxicity.…”
Section: Introductionmentioning
confidence: 99%